Comparison of axicabtagene ciloleucel and tisagenlecleucel patient CAR-T cell products by single-cell RNA sequencing - Xuefeng Wang; Paulo C Rodriguez; Frederick L Locke; Xiaoqing Yu; Marco L Davila; Salvatore Corallo; Bijal Shah; Kayla Reid; Michael D Jain; Sean J Yoder; Chaomei Zhang; Reginald Atkins; et al. (Journal for ImmunoTherapy of Cancer)
Background Autologous CD19 chimeric antigen receptor (CAR) T-cell therapy leads to durable responses and improved survival in patients with relapsed or refractory large B-cell lymphoma (R/R LBCL). Among approved CAR T-cell products, axicabtagene ciloleucel (axi-cel; CD19/CD28) has greater real-world efficacy and cytokine-associated toxicity than tisagenlecleucel (tisa-cel; CD19/4-1BB), for reasons that are poorly understood.Methods Here we report single-cell RNA sequencing (scRNA-seq) of 57 pre-infusion CAR T-cell products from axi-cel (n=39) and tisa-cel (n=18) patients treated as standard-of-care for R/R LBCL, and their biological associations with clinical outcomes. In vitro CAR manufacturing conditions mimicking those known for axi-cel and tisa-cel were performed using CD19/CD28z or CD19/4-1BBz constructs.Results ScRNA-seq revealed that axi-cel and tisa-cel are markedly different products. Axi-cel is comprised of more CD4 central memory, CD8 central memory, and CD8 effectors, whereas tisa-cel is comprised of more proliferative CD4 and CD8 cells. Across multiple T-cell subsets, axi-cel had greater expression of immune response pathways and protein synthesis and trafficking pathways versus tisa-cel. On comparison of infusion product CAR transgene-positive (CAR+) cells to CAR transgene-negative (CAR−) T cells, axi-cel CAR+ cells had vastly different gene expression than axi-cel CAR− cells. Unexpectedly, tisa-cel CAR+ cells were highly similar to tisa-cel CAR− cells. Under recapitulated CAR-T manufacturing conditions known to be used for axi-cel and tisa-cel, we found that CAR+ cells differed from CAR− cells early after manufacturing yet became more similar to CAR− cells after prolonged expansion. Prolonged time in expansion culture, as used during tisa-cel manufacturing, greatly decreased naïve and central memory T-cell subsets.Conclusions Following manufacture, axi-cel is less differentiated and has greater immune activation compared with tisa-cel, potentially accounting for its greater efficacy and toxicity in patients. Our data support the conclusion that tisa-cel is adversely affected by its manufacturing rather than by the CAR construct.